2010
DOI: 10.1007/s11999-009-1030-4
|View full text |Cite
|
Sign up to set email alerts
|

Modified L'Episcopo Tendon Transfers for Irreparable Rotator Cuff Tears: 5-year Followup

Abstract: Patients with posterosuperior cuff tears lose functional external rotation of the shoulder. Latissimus dorsi and teres major transfer is performed to restore external rotation. Twenty patients with a mean age was 55.8 ± 6 years underwent this procedure and were examined at averages of 24.7 (n = 17) and 70.6 (n = 13) months. Two patients did not improve presumably because of failure of the transfer. The Constant and Murley score increased from 55.6 to 90.4 after 2 years and to 87.9 after 5 years. The mean activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 22 publications
1
32
0
2
Order By: Relevance
“…Because muscle atrophy and fatty infiltration cannot be reversed without continuous distraction 20,21 and are known to progress even after partial rotator cuff repair, this could be one factor affecting the external rotation weakness found in our patients. Conversely, one may conclude that the mean postoperative level of external rotation evaluated (36 ) in our series is comparable to the results found 5 years after combined latissimus dorsi/teres major transfer for irreparable posterosuperior tears 22 and therefore presents an adequate result. At least a persisting suprascapular nerve neuropathy caused by traction from an incomplete rotator cuff repair may have been a reason for persisting external rotation weakness.…”
Section: Discussionsupporting
confidence: 83%
“…Because muscle atrophy and fatty infiltration cannot be reversed without continuous distraction 20,21 and are known to progress even after partial rotator cuff repair, this could be one factor affecting the external rotation weakness found in our patients. Conversely, one may conclude that the mean postoperative level of external rotation evaluated (36 ) in our series is comparable to the results found 5 years after combined latissimus dorsi/teres major transfer for irreparable posterosuperior tears 22 and therefore presents an adequate result. At least a persisting suprascapular nerve neuropathy caused by traction from an incomplete rotator cuff repair may have been a reason for persisting external rotation weakness.…”
Section: Discussionsupporting
confidence: 83%
“…121 Clinical outcomes Studies regarding the clinical outcomes of latissimus dorsi tendon transfers are summarized in Supplementary Table III. 3,15,20,23,26,29,41,[43][44][45]61,62,75,89,92,98,116,121,122 A systematic review conducted by Namdari et al analyzed 10 studies between 1992 and 2010 to determine the expected outcomes, predictive factors for success, and complications of latissimus dorsi transfers. 94 Frequency-weighted mean follow-up was 45.5 months.…”
Section: Tendon Transfersmentioning
confidence: 99%
“…[55] noted structural deterioration comparable to non-operative management, although progression was reported slower. The described osteoarthritic changes were commonly restricted in 1 or 2 stages of the Hamada classification [82], while another group [130] reported significant osteoarthritic changes with time. However, it has been reported that radiologic findings regarding arthritic degeneration are not related to the clinical outcomes [43, 54, 117].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that radiologic findings regarding arthritic degeneration are not related to the clinical outcomes [43, 54, 117]. Nevertheless joint degeneration is anticipated [43, 75, 117] due to degradation of the tenodesis effect over time [131], a finding evident in several studies that demonstrated a decrease in acromiohumeral distance in the mid [130] and long term [55, 127] in comparison to the initial postoperative outcome. It has been suggested however, that potentially LD tendon transfer may prolong the time till arthroplasty [131].…”
Section: Discussionmentioning
confidence: 99%